No change in key reef fish herbivores or reef fisher yields in Barbados a decade after the lionfish invasion - Henri Vallès; Julian Walcott; Hazel A. Oxenford (Scientific Reports, 2025)
Abstract Red lionfish, Pterois volitans, a non-native marine species with potential to cause significant damage to Caribbean coral reefs, reached Barbados in late 2011. In 2012, before lionfish became locally established, fish surveys at ten reef sites in Barbados were undertaken every four months over a year to generate baseline data. Fisher catch surveys were also undertaken at two main landing sites twice in a year. A decade later, all surveys were repeated at the same sites. Post-invasion lionfish biomass was low across most sites and increased with site depth, likely due to fishing. A comparison of reef fish biomass of selected key herbivores of high ecological and commercial importance (parrotfishes and surgeonfishes) and forage fish groups (damselfishes and wrasses) pre- and post-invasion indicated no detectable effects of lionfish on the key herbivores and wrasses, although damselfish biomass did decline with lionfish biomass increases. We also found no evidence of a decline in fisher catch rates, suggesting no negative impacts on fisher earnings. Furthermore, catch composition remained virtually unchanged for trap fishers, while lionfish had become an important component of the catch of spearfishers. Overall, our results suggest that control of lionfish through sustained fishing effectively protects key fish herbivores and might indirectly benefit reefs through a release of fishing pressure on native fishes by spearfishers now targeting lionfish.